The Effects of Beef, Chicken, or Whey Protein After Workout on Body Composition and Muscle Performance. Issue 8 (August 2018) - Sharp, Matthew H.; Lowery, Ryan P.; Shields, Kevin A.; Lane, Jason R.; Gray, Jocelyn L.; Partl, Jeremy M.; Hayes, Daniel W.; Wilson, Gabriel J.; Hollmer, Chase A.; Minivich, Julie R.; Wilson, Jacob M.
Abstract : Abstract: Sharp, MH, Lowery, RP, Shields, KA, Lane, JR, Gray, JL, Partl, JM, Hayes, DW, Wilson, GJ, Hollmer, CA, Minivich, JR, and Wilson, JM. The effects of beef, chicken, or whey protein after workout on body composition and muscle performance. J Strength Cond Res 32(8): 2233–2242, 2018—The purpose of this study was to determine the effects of postworkout consumption of beef protein isolate (Beef), hydrolyzed chicken protein (Chx), or whey protein concentrate (WPC), compared with a control on body composition and muscle performance during 8 weeks of resistance training. Forty-one men and women were randomized into 4 groups: WPC (m = 5, f = 5; age [years] = 19 ± 2, height [cm] = 171 ± 10, mass [kg] = 74.60 ± 14.19), Beef (m = 5, f = 5; age [years] = 22 ± 4, height [cm] = 170 ± 7, mass [kg] = 70.13 ± 8.16), Chx (m = 5, f = 6; Age [years] = 21 ± 2, height [cm] = 169 ± 9, mass [kg] = 74.52 ± 13.83), and Maltodextrin (control) (m = 4, f = 6; age [years] = 21 ± 2, height [cm] = 170 ± 9, mass [kg] = 73.18 ± 10.96). Subjects partook in an 8-week periodized resistance training program. Forty-six grams of protein or a control were consumed immediately after training or at similar times on off-days. Dual-energy x-ray absorptiometry was used to determine changes in body composition. Maximum strength was assessed by 1 repetition maximum for bench press (upper body) and deadlift (lower body). Power output was measured using cycle ergometer. Whey protein concentrate (52.48 ± 11.15 to 54.96 ± 11.85 kg), Beef (51.68 ± 7.61 to 54.65 ± 8.67 kg), and Chx (52.97 ± 12.12 to 54.89 ± 13.43 kg) each led to a significant increase in lean body mass compared with baseline ( p < 0.0001), whereas the control condition did not (53.14 ± 11.35 to 54.19 ± 10.74 kg). Fat loss was also significantly decreased at 8 weeks compared to baseline for all protein sources ( p < 0.0001; WPC: 18.70 ± 7.38 to 17.16 ± 7.18 kg; Beef: 16.43 ± 5.71 to 14.65 ± 5.41 kg; Chx: 17.58 ± 5.57 to 15.87 ± 6.07 kg), but not the control condition (16.29 ± 7.14 to 14.95 ± 7.72 kg). One repetition maximum for both deadlift and bench press was significantly increased for all treatment groups when compared with baseline. No differences in strength were noted between conditions. Overall, the results of this study demonstrate that consuming quality sources of protein from meat or WPC lead to significant benefits in body composition compared with control.